Tvåspråkighet i Tornedalen : mätning av kunskaper i finska - Rönmark, Walter; Wikström, Joel (Pedagogiska institutionen, 1980)
Inom ramen för det SÖ-finansierade projektet Glesbygdens skolfrågor III, utfördes tre delstudier med syfte att mäta och beskriva elevernas språkkunskaper. I denna rapport redovisas resultaten av tre utarbetade test, två som mäter aktiva färdigheter (ordkunskaps- och ordproduk-tionsprov) samt ett förståelseprov. 354 elever i åk 4 i kommunerna Haparanda, Övertorneå och Pajala ingick. Testens realiabilitet befanns vara godtagbar. Erhållna resultat stöder i stort resultaten utifrån tidigare genomförda skattningar. (Rönmark & Wikström, 1980 c). Inga skillnader i språkkunskaper med avseende på kön erhölls, däremot med avseende på kommun, tätort-glesbygd och socialgrupp. Resultaten visar att testresultaten har ett högre samband med lärarskattningar än elevskattningar. Testresultaten kommer inom ramen för projektet längre fram att ligga till grund för en differentiering mellan å ena sidan elever med passiva kunskaper i finska och å andra sidan helt svenskspråkiga elever. As a part of the project "Education in sparsely populated areas" financed by the National Board of Education three studies aiming at measuring and describing the linguistic ability of the pupils were carried out. This report accounts for the results of three constructed tests, two of them measuring active abilities (test in knowledge of words and production of words) and the third a comprehension test. 354 pupils in grade 4 in the districts of Haparanda, över-torneå and Pajala took part. The reliability of the tests was acceptable. Achieved results support on the whole the results of previously made ratings (Rönmark & Wikström, 1980). No differences in linguistic ability as regards sex were obtained whereas differences were found regarding residential areas,densely populated areas - sparsely populated areas, and social class. The results show that the tests have a higher correlation with teacher ratings than pupil ratings. Further on within the project the test results will be the basis of a differentiation between on the one hand pupils with ...